Wireless devices in nursing education - Sánchez García, Ana Belén; López Montesinos, Maria José; Fernández Alemán, José Luis (Investigación y Educación en Enfermería, 2025)
<!-- [if gte mso 9]> <![endif]--> Objective. This article sought to explore the adoption of wireless devices in university nursing teaching and address their repercussion on future professionals. Methodology. This is a bibliographical study conducted in 2011, which analyzed international publications on the use, review, application, opinion, and experimentation of wireless devices in university nursing teaching of wireless technology in nursing teaching. The following databases were used: Medline and Science@Direct. Results. A total of 503 articles were extracted and 77 were selected, of which 40 investigated the Personal Digital Assistant (PDA), 13 the clicker (Student Response Wireless System), and six the smart phone. The use of mobile devices has experienced strong growth during the last five years, especially PDAs. Conclusion. Use of mobile devices in university nursing teaching has grown in recent years, especially PDAs. <!-- [if gte mso 9]> Normal 0 21 false false false ES-CO X-NONE X-NONE <![endif]--><!-- [if gte mso 9]> <![endif]--><!-- [if gte mso 10]> <![endif]-->